HUBUNGAN ANTARA BUDAYA KERJA DAN MOTIVASI KERJA TERHADAP KINERJA GURU DI MAS NURUL HUDA SRAGI - Ali Muhajirin (UNISAN JURNAL, 2023)
The main objective in this study is to find out the madrasa head’s leadership in improving teacher discipline in MAS Nurul Huda Sragi Lampung Selatan. This type of research is a qualitative descriptive study. The data source is the madrasa head and his deputy, teachers, and students who were selected purposively and by snowball sampling. Data collection techniques used were observation, unstructured interviews and documentation. The data analysis techniques used are inductive, with steps: reducing data, presenting data, and verifying data. The conclusion of this study is that the discipline of teachers in MAS Nurul Huda Sragi Lampung Selatan is quite good as evidenced from 1) most teachers comply with madrasa rules, 2) most teachers are diligent in teaching, 3) most teachers are timely in teaching, 4) most the teacher never leaves the classroom before class ends. The teacher’s discipline was because the head of North Lampung State MAS was able to carry out his role as a good administrator, supervisor and motivator, with findings (1) as an administrator in (a) making himself a good role model, (b) being open, and (c) creating conducive work climate. (2) as a supervisor (a) provide guidance to teachers in improving the quality of learning, (b) supervise teacher performance, (c) enhance cooperation with parents, (d) evaluate the work of teachers, and (e) following up the results of teacher performance evaluations continuously. (3) as a motivator (a) provide autonomy for teachers to develop goals, materials, methods, media, and evaluation of learning, (b) provide guidance and assistance in developing teacher competencies, (c) involving teachers in every madrasah activity, (d ) receive and provide support for teachers who have creative ideas, and (e) provide strict awards and sanctions.